2013
DOI: 10.5194/isprsarchives-xl-1-w1-185-2013
|View full text |Cite
|
Sign up to set email alerts
|

Applicability Analysis of Ultra-Light Uav for Flooding Site Survey in South Korea

Abstract: Commission VI, WG VI/4KEY WORDS: UAV (Unmanned Aerial Vehicle), Flood Mapping, Ground survey, Cadastral ABSTRACT:Recently, UAV (Unmanned Aerial Vehicle) is used in a variety of fields such as the military service, fire prevention, traffic supervision, mapping, and etc. The increased demand for UAVs is typically attributed to the low manufacturing and operational costs, flexibility of the platforms to accommodate the consumer's particular needs and the elimination of the risk to pilots' lives in difficult missi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…To date, only a handful of studies have looked at real (on-site) post-event applications of UAV technology for flood event assessment and management. To the authors' knowledge, the most relevant studies are those reported in [20,21]. In [20], a LX UAV I hexacopter (Spatial Research Institute KCSC make, location), a prototype UAV for cadastral operations equipped with six rotors and blades, was used to map a 200 × 150 m area in an urban setting of Busan (South Korea) affected by the floods associated with Typhoon Sanba (14-17 September 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a handful of studies have looked at real (on-site) post-event applications of UAV technology for flood event assessment and management. To the authors' knowledge, the most relevant studies are those reported in [20,21]. In [20], a LX UAV I hexacopter (Spatial Research Institute KCSC make, location), a prototype UAV for cadastral operations equipped with six rotors and blades, was used to map a 200 × 150 m area in an urban setting of Busan (South Korea) affected by the floods associated with Typhoon Sanba (14-17 September 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the most relevant studies are those reported in [20,21]. In [20], a LX UAV I hexacopter (Spatial Research Institute KCSC make, location), a prototype UAV for cadastral operations equipped with six rotors and blades, was used to map a 200 × 150 m area in an urban setting of Busan (South Korea) affected by the floods associated with Typhoon Sanba (14-17 September 2012). The authors focused on the effectiveness of the methodology although no flood metrics were derived from the acquired imagery.…”
Section: Introductionmentioning
confidence: 99%
“…This can be similar to other ground topographical measurements used with photogrammetric techniques to estimate accurate cross-sectional measurements which are less expensive and time-demanding [52,53]. To forecast a landslide or flash flood, larger areas has to be considered as was mentioned by recent investigations including sensors and UAVs [54,55]. This requires a fixed-wing aircraft with a larger range than a rotary-wing aircraft.…”
Section: Resultsmentioning
confidence: 78%
“…Alongside classical satellite-based remote sensing studies regarding vegetation-related aspects [16] or agricultural approaches [17], modern techniques have begun to encompass the use of UAVs more frequently in geo-spatial analyses. Previous studies have proven the use and high accuracy of UAVs, especially for small areas, applied in different fields of analysis: floods [18][19][20][21][22][23][24]; geomorphology [25][26][27][28][29][30][31]; ecology [32][33][34][35][36][37][38]; archaeology and architecture [18,[39][40][41][42][43][44][45]; or glaciology [46][47][48][49]. UAVs are currently being used with increasing frequency in ecological studies, such as those seeking to determine the above-ground biomass from canopy volume or the carbon content of dryland and semi-arid ecosystems, using structure from motion (SFM) photogrammetry [50].…”
Section: Introductionmentioning
confidence: 99%